Eliciting environmental preferences of Ghanaians: an experimental approach - Yael Meroz; Andrea Morone; Piergiuseppe Morone (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
In this paper we aim - through an experimentally-adapted Contingent Valuation survey - to look into the attributes of Ghanaians willingness-to-pay for green products. This would help us addressing two main issues: first, from a theoretical point of view, we shall assess whether Ghanaians show a preference towards environmental goods - hence, countering the too poor to be green argument. Secondly, from a methodological point of view, we shall try to see if the incentive compatible CV analysis provides a good measurement of subjects willingness-to-pay for environmental premium. Our investigation provides an answer to both issues, showing how using an incentive compatible experiment produces, in the case of Ghana, reliable results and that Ghanaians consistently show that they are willing to pay an extra premium for green products.
Keywords: C9; Q5; 330; contingent valuation; experiment; incentive-compatible; Ghana; organic products; willingness to pay; Umweltbewusstsein; Biokost; Willingness to pay; Test; Low-Income Countries; Ghana